POTENSI METODE OPTIK UNTUK PENDUGAAN KANDUNGAN ANTOSIANIN PADA BUAH BLACK MULBERRY DAN STROBERI - Jajang Juansah (Jurnal Biofisika, 2013)
Estimation  of  pigment  in  plant  tissues  can  be  studied  from  optical  properties. Reflectance spectra of optics signal on black mulberry and strawberry fruit have been studied for nondestructive estimation of anthocyanin pigment content. In addition, the absorbance spectra were also studied in fruit extracts with different solvent types, ie: a combined solution of tartaric acid  and ethanol  -  chloric acid.  The results showed that there is energy absorption for  chlorophyll a in the blue area, i.e.: 465 nm-  black mulberry  and  478  nm-strawberry.  While  the  energy  absorption  for  chlorophyll  b occurs in the red region with a wavelength of 650 nm  (black mulberry) and 655 nm (strawberry). Maximum peak absorbance of anthocyanin pigments of black mulberry fruit with tartaric acid solvent had occurred at 515 nm. While  for the solvent ethanol  -hydrochloric acid has occurred at a wavelength of 519 nm.